2019
DOI: 10.1002/ps.5305
|View full text |Cite
|
Sign up to set email alerts
|

Efficient somatic and germline genome engineering of Bactrocera dorsalis by the CRISPR/Cas9 system

Abstract: BACKGROUND: Bactrocera dorsalis (Hendel), a very destructive insect pest of many fruits and vegetables, is widespread in many Asian countries. To facilitate control of this pest, it is essential to investigate its genetics and gene function using targeted gene disruption.RESULTS: Here, we describe successful targeted mutagenesis of the white and transformer genes in B. dorsalis through use of the clustered regularly interspaced short palindromic repeats/CRISPR-associated 9 (CRISPR/Cas9) system. Co-injection of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 69 publications
3
19
0
Order By: Relevance
“…For example, CRISPR-based gene drive strains could be evaluated in the future for population suppression of these important pests of livestock (Hammond et al 2016; Scott et al 2018; Kyrou et al 2018). Concha and Scott (2009) found that some fully transformed XX L. cuprina flies are fertile, as it was also described by Zhao et al (2019) for the Oriental fruit fly, Bactrocera dorsalis . Thus both XY and fully transformed XX flies could contribute to population suppression.…”
Section: Discussionsupporting
confidence: 66%
“…For example, CRISPR-based gene drive strains could be evaluated in the future for population suppression of these important pests of livestock (Hammond et al 2016; Scott et al 2018; Kyrou et al 2018). Concha and Scott (2009) found that some fully transformed XX L. cuprina flies are fertile, as it was also described by Zhao et al (2019) for the Oriental fruit fly, Bactrocera dorsalis . Thus both XY and fully transformed XX flies could contribute to population suppression.…”
Section: Discussionsupporting
confidence: 66%
“…We synthesized two sgRNAs, named BdWhite‐g1 and BdWhite‐g2 , which are located in exons 1 and 3 respectively, and we injected a mixture of Cas9 protein and sgRNA, transcribed in vitro , into fresh eggs that resulted in highly efficient editing of the BdWhite locus. We observed a 100% editing frequency in the surviving flies of the BdWhite‐g2 ‐injected generation; this 100% germline transmission rate was higher than reported for other insects (Wang et al ., ; Xue et al ., ; Chen et al ., ), including B. dorsalis (Zhao et al ., ; Zheng et al ., ; Sim et al ., ). The high mutation efficiency may be due to the high concentration of sgRNA (500 ng/μl) used in this study, and rapid injection of the embryos following oviposition (within 1 h) and the injection of cas9 protein into embryos, rather than cas9 mRNA or plasmid (Zhao et al ., ; Zheng et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…The CRISPR/Cas9 system is a simple and efficient genome‐editing technique that shows significant potential for genetic editing and exploring gene function in nonmodel animals (Choo et al ., ; Wang et al ., ; Xue et al ., ; Chen et al ., ). The system has been used to edit genomes of several Tephritidae, including B. dorsalis (Meccariello et al ., ; Zhao et al ., ; Zheng et al ., ; Li and Handler, ; Sim et al ., ), and here we successfully applied it to study the function of the white gene in B. dorsalis . We synthesized two sgRNAs, named BdWhite‐g1 and BdWhite‐g2 , which are located in exons 1 and 3 respectively, and we injected a mixture of Cas9 protein and sgRNA, transcribed in vitro , into fresh eggs that resulted in highly efficient editing of the BdWhite locus.…”
Section: Discussionmentioning
confidence: 99%
“…In Bactrocera dorsalis , this technology has been proven effective several times in the study of gene function (Baia et al ., 2019;X. Chen et al ., 2021;Wanget al ., 2020;Zhao et al ., 2019;Zheng et al ., 2019). CRISPR-Cas9 also offers the advantage of a diversity of Cas9 systems depending on the bacterial source (Khalil, 2020) and flexibility of use as DNA in a plasmid (Zheng et al , 2019), as injected mRNA Wang et al ., 2020) or directly as protein (Baia et al , 2019).…”
Section: The Crispr-cas9 Systemmentioning
confidence: 99%